NUMERICAL SIMULATION OF THE CATASTROPHIC EARTHQUAKE AND TSUNAMI IN CHILE ON 9 MAY 1877 - Mazova R.Kh; Baranova N.A; Alekseev D.A.; Lobkovsky L.I.; J. F.; Oses G. A.; Gustavo Oses A. (Science of Tsunami Hazards, 2022)
In this paper, on the basis of the available historical data and geodynamic studies, numerical simulation of the historical catastrophic earthquake and tsunami of May 9, 1877 is carried out by making use the so called “keyboard” geodynamical model providing the computational formalism for seismic cycles and crustal block motion analysis. 23 scenarios of the kinematic movement of the keyboard blocks were implemented, when the earthquake source was fragmented from larger to smaller segments. Using the proposed methodology, for each scenario, the generation of a tsunami source is simulated and the computation of wave fields up to the 5-meter isobath is carried out. Analysis of the entire set of simulated earthquake scenarios makes it possible to choose a tsunamigenic earthquake scenario with the most adequate characteristics of tsunami waves in the coastal zone. The results obtained are compared with both historical data and those obtained for this event by other authors using various numerical models. Large-magnitude earthquakes in northern Chile andsouthern Peru occur every 108 years on average. It should be noted that over 143 years since the catastrophic earthquake of May 9, 1877, any similar events were completely absent. In 2007, a 7.7 Mw earthquake occurred near Tocopilla, and in 2014 a catastrophic M = 8.1 earthquake hits Pisagua. It is believed that only part of the energy accumulated over 143 years has been released during those events, while most of it is yet to be released. Thus, we can conclude that a serious tsunami hazard exists for all coastal cities of southern Peru and northern Chile.